Health service utilization among Bangladeshi workers in Malaysia - Uddin, Md Sayed; Md. Noon, Hazizan (IIUM Press, International Islamic University Malaysia, 2017)
This book is based on an empirical study of Bangladeshi workers’ use of healthcare services in Malaysia. It is guided by Andersen’s (1968, 1995) Behavioural Model of population characteristics frameworks that consist of three factors that predispose services use (e.g. demographic), enabling use (financial resources) and need for care. The study also investigated the barriers that Bangladeshi temporary workers perceive to prevent their access to healthcare services. It further assessed their present health status in Malaysia and factors affecting their health. A questionnaire was administered to 300 respondents involved in construction, manufacturing and services sectors. The study employed two statistical methods. First, Chi-square test was used to find the significant association among variables. Second, binary logistic regression analysis was used to test the hypotheses. The key finding indicates that Bangladeshi workers’ education level is a strong significant predictor of maintaining sound health condition in Malaysia. In contrast, their health deteriorates because of long duration of stay in Malaysia. This study reveals that many Bangladeshi workers (n-212) are not consistent in visiting doctors, hospitals or clinics and emergency rooms when they experience sickness in the past one year. The reason is that the majority of them (n=131) were found to practice self-treatment or self-medication to overcome various illnesses. Further, the majority of the workers do not get any medical facility from their employers. The theoretical implication of Andersen’s behavioural model is that predisposing and need factors are found significantly and positively associated with the use or visit to doctors, hospitals or clinics in one year. The findings reveal that predisposing factors, including age and marital status; and need factors, including self-rated health status, suffering chronic illnesses in the previous one year, have the greatest impact on healthcare utilization. Bangladeshi workers’ who are married and have better health condition, suffer from chronic illnesses in the last one year were more likely to use healthcare services. It is also found that the Andersen’s model is most useful for predicting doctor, hospital or clinic visits in one year. However, Andersen’s behavioural model for Bangladeshi migrant workers was not a good framework for use or visit to emergency rooms and overnight stay at the hospital. The major findings indicate that healthcare providers do not understand workers’ problems, high medical costs, self-treatment and lack of transportation which are the primary barriers for the majority of respondents from using healthcare services. According to binary logistic regression analysis, there is no statistical significance for the relationship between education, duration of stay in Malaysia and workers’ involvement in three working sectors with any types of healthcare services utilization. Finally, the study suggests that adequate measure should be taken to provide pre-departure training related to existing healthcare system in Malaysia including existing health insurance coverage and extension of services to the expected migrant workers. We would like to express our gratitude to all those who contributed directly or indirectly to the completion of this book. In particular, we would like to record our deepest and profound gratitude to Professor Dr. Jamil Farooqui, for his precious inputs and support. We also would like to thank Professor Dr. A.H.M Zehadul Karim, an expert on this topic who provided us valuable feedback. We wish to express our sincere gratitude to Dr. Nor Azlin Binti Tajuddin, Head of the Department of Sociology and Anthropology for her encouragement and generous support. Our thanks are also due to Mr. Md. Rais Hasan Sarowar (Political Counsellor cum Acting High Commissioner), Bangladesh High Commission Malaysia (Kuala Lumpur) for the People’s Republic of Bangladesh for his permission and co-operation for data collection in the Bangladesh High Commission office, Kuala Lumpur Office, Malaysia. Last but not least, we would like to express our sincere thanks to Mr. Fazlul Karim, Mr. Motin and Mr. Fozlu (Senior Bangladeshi workers) for their cooperation and support for the data collection process.